Subcutaneous ICD screening with the Boston Scientific ZOOM programmer versus a 12‐lead ECG machine - Chang, Shu C.; Patton, Kristen K.; Robinson, Melissa R.; Poole, Jeanne E.; Prutkin, Jordan M. (Pacing and clinical electrophysiology, 2018)
Background The subcutaneous implantable cardioverter‐defibrillator (S‐ICD) requires preimplant screening to ensure appropriate sensing and reduce risk of inappropriate shocks. Screening can be performed using either an ICD programmer or a 12‐lead electrocardiogram (ECG) machine. It is unclear whether differences in signal filtering and digital sampling change the screening success rate. Methods Subjects were recruited if they had a transvenous single‐lead ICD without pacing requirements or were candidates for a new ICD. Screening was performed using both a Boston Scientific ZOOM programmer (Marlborough, MA, USA) and General Electric MAC 5000 ECG machine (Fairfield, CT, USA). A pass was defined as having at least one lead that fit within the screening template in both supine and sitting positions. Results A total of 69 subjects were included and 27 sets of ECG leads had differing screening results between the two machines (7%). Of these sets, 22 (81%) passed using the ECG machine but failed using the programmer and five (19%) passed using the ECG machine but failed using the programmer (P < 0.001). Four subjects (6%) passed screening using the ECG machine but failed using the programmer. No subject passed screening with the programmer but failed with the ECG machine. Conclusion There can be occasional disagreement in S‐ICD patient screening between an ICD programmer and ECG machine, all of whom passed with the ECG machine but failed using the programmer. On a per lead basis, the ECG machine passes more subjects. It is unknown what the inappropriate shock rate would be if an S‐ICD was implanted. Clinical judgment should be used in borderline cases.